Pre-Service Computer Teachers’ Tendencies Towards the Use of Mobile Technologies: A Technology Acceptance Model Perspective - Çakıroğlu, Ünal; Gökoğlu, Seyfullah; Öztürk, Mücahit (EDEN Digital Learning Europe, 2017)
Abstract Drawing on the Technology Acceptance Model (TAM), this exploratory study examines the preservice teachers’ adoption of mobile technologies through the factors of current use, instructional use and future use in their teaching practices. Participants were 466 pre-service computer teachers enrolled at a public university in Turkey. A questionnaire developed by the researchers was used to collect data. Results indicated that the current use and instructional use factors had a strong positive correlation and also there was a similar correlation with the factor of future use and current use. Relationships between current, instructional, and future use of mobile technologies explained within the context of perceived usefulness, ease of use, and behavioural intention constructs of the TAM.
Keywords: 4. Education